Analysis of defence activities in Hungarian national handball league matches with a focus on gender and positions - Marczinka, Z.; Csáki, I. (Journal of Physical Education and Sport, 2023)
The aim of our research is to evaluate defence activities by analysing the Hungarian first league handball matches and to compare the results between positions and genders. The matches from the 2019/20 league season that were close (within a 6-goal difference) were chosen; thus, 5 men's and 5 women's matches were selected. Within a match, both the home and away teams were analysed; a total of 20 teams were analysed (n = 20). In our study, a post-match observation method was used. To ensure accurate observations, a total of 120 observers participated in the analysis of matches; thus, each observer focused only on one player from one team playing in one specific position in one match (i.e., 6 data collectors per team; a total of 12 people per match). The following variables were observed: tackling, blocking, stealing the ball and tactical activity. In our research, SPSS 25.0 statistical software was used to visualize the results. Descriptive statistics were used to present the mean and standard deviation results. A two-sample t-test was used to detect differences between genders, and a one-point analysis of variance was used to demonstrate differences between positions. A general examination of tackling revealed that diverting tackles were used three times as often in matches than halting tackles and were significantly more frequently performed on the ground than in the air. When comparing gender in the case of blocking goal shots, it was found that males showed significantly higher values than females for the blocking jump shot variable. No significant difference was found when analysing the statistics by gender for stealing the ball. When analysing tactical activity by gender, a significant difference was found only for forcing a technical error, in favour of male players. Our results provide valuable insights for the design of optimal training plans and draw attention to the importance of differentiation by position, which clearly reinforces the importance of individual training in the preparation of professional handball players.